2007
DOI: 10.1159/000107231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Administration of Betamethasone on Peripheral Arterial Development in Fetal Rabbit Lungs

Abstract: Objectives: Glucocorticoids promote lung maturation and reduce the incidence of respiratory distress syndrome in premature newborns. We hypothesized that betamethasone (BM), which is known to induce thinning of the alveolar walls, would also thin the arterial media and adventitia of intra-parenchymatic vessels in developing rabbit lungs. Study Design: 112 fetuses from 21 time-mated, pregnant, giant white rabbits received maternal injections of BM at either 0.05 or 0.1 mg/kg/day on days 25–26 of gestational age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 55 publications
(43 reference statements)
3
26
1
2
Order By: Relevance
“…Both chorioamnionitis and antenatal steroids improve postnatal lung function. Some studies have shown that maturational changes can occur at the expense of normal alveolar development (14); others report that antenatal betamethasone did not affect alveolarization (23) and that it even decreased both pulmonary hypertension (24) and ventilation-induced lung injury (25). Although antenatal corticosteroid administration worsened chorioamnionitis-related lung development impairment in rabbits, suggesting an additive effect on fetal lung alveolar simplification (8), betamethasone treatment after intra-amniotic LPS injection enhanced fetal lung maturation in lambs (26).…”
Section: Chorioamnionitis and Steroid For Bpdmentioning
confidence: 99%
“…Both chorioamnionitis and antenatal steroids improve postnatal lung function. Some studies have shown that maturational changes can occur at the expense of normal alveolar development (14); others report that antenatal betamethasone did not affect alveolarization (23) and that it even decreased both pulmonary hypertension (24) and ventilation-induced lung injury (25). Although antenatal corticosteroid administration worsened chorioamnionitis-related lung development impairment in rabbits, suggesting an additive effect on fetal lung alveolar simplification (8), betamethasone treatment after intra-amniotic LPS injection enhanced fetal lung maturation in lambs (26).…”
Section: Chorioamnionitis and Steroid For Bpdmentioning
confidence: 99%
“…Examples of investigated interventions are administration of corticosteroids, in utero repair of the diaphragmatic defect and fetal tracheal occlusion or a combination of the two [11,12] . In utero repair has been attempted with either primary closure of the defect by using a patch (immediate reduction) or secondary closure by using the slow 'silo' reduction technique in which the opening gradually reduces as the fetus grows [13][14][15] .…”
Section: Surgical Modelsmentioning
confidence: 99%
“…In addition, reciprocal chromosome painting using human chromosomes showed complete homology in more than three chromosomes (7). Based on these observations, a rabbit seems to be a more appropriate model compared with other classical animal models for studying human lung development and various gene expressions during intrauterine and early neonatal life (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 92%